Online geospatial platform for the collection of the irrigation fee - Martínez Miramontes, José Gabriel; Mejía Sáenz, Enrique; Chávez Morales, Jesus; Salgado Tránsito, Jorge Arturo (Revista Mexicana de Ciencias Agrícolas, 2020)
In Mexico, there is an area of 6.5 million hectares under irrigation, made up of 3.3 million corresponding to 86 Irrigation Districts and the remaining 3.2 million to more than 40 thousand irrigation units. Due to the fact that in the country’s irrigation districts the possession of land and the uses of soil and water are dynamic, it is necessary to have a continuous update of their user registers. The models of the Geographic Information System, at the parcel level of the irrigation districts of Mexico, constitute a valuable tool that needs to be capitalized in the use of different applications to improve the development of the activities that involve the attention of said districts. In this work, based on the update of the user registry and the cadastre in the GIS model of module 5 Tepatepec of the Irrigation District 03 Tula, Hidalgo, the system for collecting the irrigation service fee is integrated into a geospatial platform online. This will allow obtaining a register of users, cadastre, cultivated areas and pattern of crops in real time, updated through the process of charging the irrigation service fee.
Keywords: geographic information systems; real time; user registry